(untitled) (The Pretoria Student Law Review, 2021)
A rather curious case resurfaces regarding a post-liberal reading of the Constitution, where the majority of the Constitutional Court (I would most humbly contend) failed to apply the correct reading of the Constitution and created a backdoor for the legislature to formally discriminate against a category of persons. What case would my bleeding liberal hart then, as a friend often so kindly phrases it, be aggrieved about? The one atop the shrine of annoyance to many religious and more conservative members of our post-apartheid society: Minister of Home Affairs v Fourie I believe the lone dissenter in the matter, former Justice O’Regan, applied the correct reading of section 39(2) of the Constitution by using the so-called principle of ‘reading in’ to create a gender-neutral definition of marriage in the Constitution. Section 39(2) of the Constitution requires a court to promote the ‘spirit, purport and objects’ of the Bill of Rights when interpreting legislation or developing the common law. Former Justice O’Regan was in lone dissent regarding the appropriate remedy pertaining to the unconstitutionality of the definition of marriage in the Marriage Act. She would have had the order with immediate effect and alter the common law definition of marriage, traditionally being the lifelong union of one man and one woman to the exclusion of all others while it lasts, be gender neutral by utilising the so-called principle of ‘reading in’. Instead, the majority of the court gave the legislature time to correct the definition of marriage, and formally discriminate against lesbian, gay, bisexual and transgender persons. The legislature enacted the Civil Union Act. Under the Civil Union Act, spouses can elect to have their union known as a marriage or a civil union. I employ the phrase ‘formally discriminate’, because for the most part the Civil Union Act brings about the same consequences as the Marriage Act. There however seems to lurk some sense of inferiority in the air about a civil union. Generally, albeit a somewhat anecdotal claim (but has nonetheless become a finding of fact in American law), society does not regard a civil union as a marriage. The question arising can be concisely formulated as follows: although a civil union can be registered as a marriage under section 12(3) of the Civil Union Act, does such registration give rise to the same cultural and traditional symbolic values associated with that of marriage?